Kunjungan ANC, posyandu dan imunisasi dengan kejadian stunting pada balita di Kabupaten Buton Tengah - Agus Darmawan; Reski Reski; Rininta Andriani (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
Stunting is a problem of nutritional status in children. Utilization of health services in the form of ANC visits, Integrated Health Service Post (IHSP), and poor immunizations is very likely to affect the incidence of stunting in toddlers. This study aims to determine the relationship between ANC visits, Integrated Health Service Post (Posyandu) visits, and immunization status with the incidence of stunting under five. The study used a cross-sectional design and was conducted in 2019. The sample was taken by stratified random sampling of as many as 81 toddlers. Primary data is data processed by questionnaires through direct question and answer, while secondary data is sourced from Public Health Center data. Data processing uses univariate and bivariate analysis through editing, coding, tabulating, data entry, and data cleaning—statistical test using Chi-Square, at 95% CI. The results showed that the history of ANC visits had a relationship with the incidence of stunting (p= 0,044), visits of IHSP had a relationship with the incidence of stunting (p= 0,001), and immunization status had a relationship with the incidence of stunting (p= 0,005). The conclusion is that the history of ANC visits, visits to IHSP, and immunization status have a relationship with the incidence of stunting.